Símbolo e/ou representação: um mapeamento metapsicológico - Levy, Ruggero; Keidann, Carmem Emilia; Dal Zot, Jussara Schestatsky; Menegat, Maria Clélia de Barros; Neuhaus, Marli Donadussi; Santis, Miriam F. Barros de; Lago, Patrícia Fabrício (Revista de Psicanálise da SPPA, 2013)
Os autores discutem os conceitos de representação e simbolização inseridos em seus contextos metapsicológicos. Assim, exploram os modelos psicanalíticos freudiano, kleiniano e bioniano, respectivamente, buscando compreender a origem lógica desses conceitos, contrastá-los, ver seus desenvolvimentos e discutir as implicações teóricas, clínicas e técnicas. No âmbito freudiano, apoiam-se em Freud, Garcia-Roza, Laplanche e Pontalis, Green e Botella e Botella; no campo kleiniano utilizam Klein, Jones, Ferenczi, Susan Isaacs; e, finalmente, na esfera bioniana, Meltzer, Bion, Ogden e Ferro. Por fim, descrevem algumas de suas repercussões na clínica e técnica psicanalíticas. Symbol and/or representation: a metapsychological mapping The authors discuss the concepts of representation and symbolization inserted in their metapsychological contexts. This way, they explore the freudian, kleinian and bionion psychoanalytic model respectively, searching to understand the logic origin of these concepts, as well as contrast them, observe their development and discuss the clinical, theoretical and technical implication. In the freudian scope, the authors rely on Freud, Garcia-Roza, Laplanche e Pontalis, Green and Botella & Botella; in the kleinian field, they make use of Klein, Jones, Ferenczi, Susan Isaacs; and finally, in the bionion perspective, Meltzer, Bion, Ogden and Ferro. Lastly, it is described some of their repercussion in the psychoanalytic clinic and technique. Keywords: drive, representation, representation of thing, representation of word, intrapsychic, symbol, symbolization, object relation, intersubjective.